Physical Education as a Character Formation in Paringin City Elementary School in the Modern Era - Irmayanti; Arie Rakhman; Akhmad Amirudin (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This research seeks to explore the role of physical education in shaping students' character at Paringin City Elementary School in the contemporary era. The examined character encompasses elements of religiosity, honesty, tolerance, discipline, and responsibility. This research employs a quantitative descriptive approach using a survey technique, in which questionnaires are distributed to fifth-grade students across 10 elementary schools in Paringin City. The gathered data is analyzed using the percentage technique and presented through tables and bar charts to depict each category in the character development process.. The study results indicate that physical education significantly contributes to shaping students' character. The majority of the analyzed character aspects fall within the categories of "excellent" to "good", The responsibility aspect achieved the highest percentage at 84%, followed by honesty at 77%. These findings reaffirm that physical education contributes not only to physical development, but also serves as an effective tool for character development. Hence, to further instill character values in students, it is essential to enhance and optimize physical education teaching methods.